Ameliorative effect of Boesenbergin A, a chalcone isolated from Boesenbergia rotunda (Fingerroot) on oxidative stress and inflammation in ethanol-induced gastric ulcer in vivo. (28th October 2020) - Mohan, Syam; Hobani, Yahya Hasan; Shaheen, Emad; Abou-Elhamd, Alaa Sayed; abdelhaleem, Aymen; Alhazmi, Hassan A.; Abdelwahab, Siddig Ibrahim
Abstract: Ethnopharmacological relevance: Boesenbergia rotunda (L.) Mansf. Kulturpfl., previously known as Boesenbergia pandurata (Family: Zingiberaceae) is a ginger species, locally known as fingerroot. It is an integral part of Southeast Asian traditional medicine in alleviating many gastrointestinal disorders such as flatulence, carminative, stomach ache, dyspepsia, and peptic ulcer. Aim of the study: Earlier we have investigated the cytoprotective effect of Boesenbergia rotunda extract. In the present study, we investigated the gastroprotection activity of Boesenbergin A (BA), a chalcone isolated from Boesenbergia rotunda extract in ethanol-induced ulcer model in rats. Besides, the contribution of anti-inflammatory and anti-oxidant ability of BA as probable mechanisms involved in the anti-ulcer activity, also been studied. Materials and methods: BA was orally administered in rats before ulcer induction with ethanol. The lesions of the gastric mucosa were evaluated macroscopically and histopathologically. The efficiency of BA in mucus production, NO production, PGE2 synthesis, mucosal nonprotein sulphydryls, glutathione (GSH) level, and lipid peroxidation (MDA) level were studied. The involvement of the anti-inflammatory capacity of BA was analyzed by using the measurement of cytokines such as TNF-α and IL-6. Finally, the expression of biomarkers such as HSP 70 and iNOS was analyzed at the transcriptional and translational levels. Results: We confirmed the protective capacity of BA via the reduction of ulcerated and haemorrhagic areas. It has induced the protection through lowering GSH, MDA and increased NP-SH level. The plasma NO levels were significantly less in BA treated rats. Both cytokines TNF-α and IL-6 were decreased together with elevated PGE2 . Upregulation of HSP and downregulation of iNOS were determined in immunohistochemical and gene expression studies Conclusions: The current results suggest that the prophylactic effect found with BA is due to (i) boosting of gastric mucus production and suppression of inflammatory mediators, via pro-inflammatory cytokines and (ii) modulating the oxidative stress response. The usefulness of Boesenbergia rotunda in folk medicine in treating ulcers partially could be due to the presence of this chalcone. Graphical abstract: Image 1